Facile Synthesis of Sub-20 nm Silver Nanowires through a Bromide-Mediated Polyol Method - Da Silva, Robson Rosa [UNESP]; Yang, Miaoxin; Choi, Sang-Il; Chi, Miaofang; Luo, Ming; Zhang, Chao; Li, Zhi-Yuan; Camargo, Pedro H. C.; Ribeiro, Sidney José Lima [UNESP]; Xia, Younan (American Chemical Society (ACS), 2016)
Essentially all of the Ag nanowires reported in the literature have sizes larger than 30 nm in diameter. In this article, we report a simple and robust approach to the synthesis of Ag nanowires with diameters below 20 nm and aspect ratios over 1000 using a one-pot polyol method. The Ag nanowires took a penta-twinned structure, and they could be obtained rapidly (<35 min) and in high morphology purity (>85% of the as-obtained solid product) under atmospheric pressure. The key to the success of this synthesis is to restrain the nanowires from lateral growth by employing both Br- ions and poly(vinylpyrrolidone) with a high molecular weight of 1»300»000 g/mol to cap the {100} side faces, together with the use of a syringe pump to slowly introduce AgNO3 into the reaction solution. By optimizing the ratios between the capping agents and AgNO3, we were able to slow down the reduction kinetics and effectively direct the Ag nanowires to grow along the longitudinal direction only. The nanowires showed great mechanical flexibility and could be bent with acute angles without breaking. Because of their small diameters, the transverse localized surface plasmon resonance peak of the Ag nanowires could be pushed down to the ultraviolet region, below 400 nm, making them ideal conductive elements for the fabrication of touch screens, solar cells, and smart windows.
Keywords: kinetic control; nanowires; polyol method; silver; surface plasmon resonance